Ceramides and diabetes mellitus: an update on the potential molecular relationships. Issue 1 (7th April 2019) - Yaribeygi, H.; Bo, S.; Ruscica, M.; Sahebkar, A.
Abstract: Recent evidence suggests that ceramides can play an important pathophysiological role in the development of diabetes. Ceramides are primarily recognized as lipid bilayer building blocks, but recent work has shown that these endogenous molecules are important intracellular signalling mediators and may exert some diabetogenic effects via molecular pathways involved in insulin resistance, β‐cell apoptosis and inflammation. In the present review, we consider the available evidence on the possible roles of ceramides in diabetes mellitus and introduce eight different molecular mechanisms mediating the diabetogenic action of ceramides, categorized into those predominantly related to insulin resistance vs those mainly implicated in β‐cell dysfunction. Specifically, the mechanistic evidence involves β‐cell apoptosis, pancreatic inflammation, mitochondrial stress, endoplasmic reticulum stress, adipokine release, insulin receptor substrate 1 phosphorylation, oxidative stress and insulin synthesis. Collectively, the evidence suggests that therapeutic agents aimed at reducing ceramide synthesis and lowering circulating levels may be beneficial in the prevention and/or treatment of diabetes and its related complications. What's new?: Ceramides are building blocks of cellular lipid bilayers and have been causally implicated in the pathophysiology of diabetes. Recent evidence suggests that ceramides act as intracellular signalling molecules and may exert diabetogenic effects via pathways involved in insulin resistance, β‐cell apoptosis and inflammation. We present the mechanistic evidence for the role of ceramides in diabetes. New therapeutic agents that lower plasma levels of ceramides may be beneficial in the prevention and/or treatment of diabetes and its related complications.